The investigation of novel marine microorganisms for the production of biologically active metabolites - Sunkel, Vanessa Ann (Rhodes University, Faculty of Pharmacy, Pharmacy, 2009)
New drugs, particularly antibiotics, are urgently required to combat the increasing problem of antibiotic resistant human pathogens. Due to the scarcity of products available today, the pharmaceutical industry is now under pressure to reassess compounds derived from plants, soil and marine organisms. Pharmaceutical companies are showing renewed interest in marine biotechnology as the oceans represent a rich source of both biological and chemical diversity of novel molecular structures with anti-cancer, anti-inflammatory and antibiotic properties. Formerly unexplored locations, such as deep ocean sediments, show great potential as a source of genetically novel microorganisms producing structurally unique secondary metabolites. In this research, a metabolite producing marine Pseudoalteromonas strain, known as AP5, was initially used to develop methods for the detection, optimisation of production and extraction of bioactive metabolites from other potentially novel marine isolates. Two hundred and seventy six (276) marine isolates from water and sediment samples from the Antarctic Ocean and Marion Island were isolated. Ten visually different isolates were screened for bioactivity against Gram-positive and -negative bacteria, fungi and yeast. Three out of the 10 isolates, WL61 , WL 114 and WL 136, appeared to be novel Streptomyces spp. showing activity against different test organisms. Many of these marine microorganisms are difficult to culture in the laboratory, particularly when they are cultivated continuously in shake flasks as they can stop producing bioactive compounds. The cultivation of marine isolates in bioreactors may be a more beneficial process for the optimisation of metabolite production compared to conventional liquid fermentation techniques whereby the solid-liquid-air interface of membrane bioreactors can imitate the natural environment of microbes. The membrane bioreactor system is a stable growth environment with low shear that supports steady-state biofilm growth consisting of a high cell density due to a high mass transfer of nutrients and oxygen to the cells. This approach was employed and isolates WL61, WL114 and WL136 were immobilised onto ceramic membranes using Quorus single fibre bioreactors (SFR). The SFRs were used to establish the most suitable growth medium for continuous secondary metabolite production. The best growth conditions were applied to the Quorus multifibre bioreactor (MFR) for scale up of biologically active metabolites, highlighting the potential of bioreactor technology for use in bioprospecting for isolating and screening novel and known organisms for new and interesting natural products. Furthermore, the Quorus MFR was shown to be suitable for the production of high yields of antimicrobial metabolites and is an efficient new fermentation production system. Purification by HPLC fractionation was used to characterise four major compounds from isolate WL 114 extracts. NMR structure elucidation identified one of the two primary compounds as Bisphenol A. The complete chemical structure for the second potent bioactive compound could not be determined due to the low concentration and volume of material.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Antibiotics; Drugs -- Research; Metabolites; Marine biotechnology; Marine metabolites -- Therapeutic use; Microorganisms -- Effect of drugs on; Penicillium